2018
DOI: 10.1111/php.12946
|View full text |Cite
|
Sign up to set email alerts
|

Review on Nonoccupational Personal Solar UV Exposure Measurements

Abstract: Solar ultraviolet (UV) radiation follows people during their whole life. Exposure to UV radiation is vital but holds serious risks, too. The quantification of human UV exposure is a complex issue. UV exposure is directly related to incoming UV radiation as well as to a variety of factors such as the orientation of the exposed anatomical site with respect to the sun and the duration of exposure. The use of badge-sensors allows assessing the UV exposure of differently oriented body sites. Such UV devices have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 113 publications
(153 reference statements)
0
39
0
Order By: Relevance
“…A recent review of 55 studies on Non-Occupational Personal Solar UV Exposure measurements suggests that knowledge on exposure of humans to UV radiation has clearly increased, especially in the past decade. 230 The solar UV radiation environment relevant to recreational boaters on oceans was simulated with radiative transfer models that take scattering and absorption process in the atmosphere and the ocean into account. 231 231,232 also suggest that swimming in the ocean provides little protection from sun exposure.…”
Section: Personal Exposurementioning
confidence: 99%
“…A recent review of 55 studies on Non-Occupational Personal Solar UV Exposure measurements suggests that knowledge on exposure of humans to UV radiation has clearly increased, especially in the past decade. 230 The solar UV radiation environment relevant to recreational boaters on oceans was simulated with radiative transfer models that take scattering and absorption process in the atmosphere and the ocean into account. 231 231,232 also suggest that swimming in the ocean provides little protection from sun exposure.…”
Section: Personal Exposurementioning
confidence: 99%
“…Polysulphone film dosimetry has been used extensively in personal UVR exposure studies . For the current study, involving 29 individual participants, daily sets of miniaturized PS dosimeters and paper sun diaries were preferred for recording personal exposure over UVR electronic dosimeters.…”
Section: Methodsmentioning
confidence: 99%
“…Further details of these, and more recent studies, can be found in excellent reviews on personal solar UV exposure in both children [48] and adults [49].…”
Section: Applications Of Polysulphone Film Dosimetrymentioning
confidence: 99%